Biodiversity and safety profiling of indigenous Enterococcus faecalis from Nem Chua, a traditional Vietnamese fermented pork ecosystem - NGUYEN PHUONG THUY; NGUYEN VIET KHANH HUNG; VO NGUYEN NGOC NHU (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Thuy NP, Hung NVK, Nhu VNN. 2026. Biodiversity and safety profiling of indigenous Enterococcus faecalis from Nem Chua, a traditional Vietnamese fermented pork ecosystem. Biodiversitas 27 (1): d270136. https://doi.org/10.13057/biodiv/d270136. Traditional Vietnamese fermented pork (Nem Chua) represents a specialized ecological niche, yet the microbial biodiversity and safety profiles of its non-conventional Lactic Acid Bacteria (LAB) remain insufficiently characterized for functional applications. This study explored the microbial reservoir of Nem Chua to isolate and evaluate indigenous LAB with biotechnological potential. Through a systematic multi-stage screening pipeline of 50 artisanal samples, an initial pool of 59 isolates was narrowed to 26 candidates based on functional and safety filters. Enterococcus faecalis NC5 was ultimately selected as the optimal candidate due to its superior ecological fitness and validated safety status. Molecular identification confirmed 100% identity with E. faecalis. NC5 demonstrated exceptional gastrointestinal resilience, maintaining viability of 4.32±0.05 Log CFU/mL at pH 2.0 and 3.82±0.02 Log CFU/mL in 1.0% bile salts. Furthermore, it exhibited potent broad-spectrum antagonism against Escherichia coli, Salmonella typhimurium, and Staphylococcus aureus. Safety profiling confirmed γ-hemolytic activity, suggesting the strain’s potential as a protective starter culture. Molecular identification based on partial 16S rRNA gene sequencing confirmed NC5 as E. faecalis with 100% sequence similarity to reference strains in GenBank. These findings suggest that E. faecalis NC5 is a robust and safe autochthonous component of the natural Nem Chua microbiota. This research highlights the vital role of preserving fermented-food biodiversity to enhance the safety and functionality of traditional Southeast Asian food systems.